Yoga untuk Mengurangi Nyeri Haid Primer pada Remaja Putri - Windayanti, Hapsari; Khayati, Yulia Nur; Veftisia, Vistra; Widyaningsih, Ari; Dewi, Maya Kurnia; Izzah, Lu’luul Fitrotul; Mulyani, Mulyani; Aprilia, Nia; Sabwan, Indriani Kasih; Sari, Lidia Arjulia (UNIVERSITAS NGUDI WALUYO, 2021)
The results of the study show that educational technology has a very important role in the 4.0 education era, as seen from the use of educational technology products such as E-learning, applications, self study platforms that are in line with the demands of education 4.0. especially during the covid-19 pandemic which requires everyone to be able to master technology to make it easier to get information. The information here is related to how to handle dysmenorrhea or primary menstrual pain which is usually experienced by women of childbearing age. Although most period pain can go away on its own, but if it lasts all day, it will interfere with activities. Primary dysmenorrhea is menstrual pain that is not based on pathological conditions, while secondary dysmenorrhea is menstrual pain based on pathological conditions such as the discovery of endometriosis or ovarian cysts. Through regular yoga practice, it will provide great benefits such as reducing pain during menstruation. Community service consists of several stages, namely the first stage of determining the sample consisting of 10 teenagers with the age of 12-19 years. The second stage determines the measuring instrument used is a questionnaire on the level of respondents' knowledge about the symptoms of menstrual pain and skills to reduce menstrual pain during menstruation. The third stage is lectures and discussions as well as online practice through Whatsapp Groups. The fourth stage is applying yoga by providing online assistance and evaluating how each teenager who is a sample sends a video of the application of yoga.ABSTRAKHasil studi menunjukan bahwa teknologi pendidikan mempunyai peranan yang sangat penting dalam era pendidikan 4.0, terlihat dari pemanfaaatan produk teknologi pendidikan seperti e-learning, aplikai, platform self study yang selaras dengan tuntutan pendidikan 4.0. terlebih pada masa pandemi covid-19 yang menuntut setiap orang untuk bisa menguasai teknologi agar lebih mudah mendapatkan informasi. Informasi disini terkait tentang cara penanganan disminore atau nyeri haid primer yang biasanya dialami wanita usia subur. Meskipun kebanyakan nyeri haid dapat hilang dengan sendirinya, tetapi jika berlangsung sepanjang hari, akan mengganggu aktivitas. Dismenore primer merupakan nyeri haid yang tidak didasari kondisi patologis, sedangkan dismenore sekunder merupakan nyeri haid yang didasari dengan kondisi patologis seperti ditemukannya endometriosis atau kista ovarium. Melalui latihan yoga secara teratur, akan memberikan manfaat yang besar seperti dapat mengurangi nyeri saat haid. Pengabdian masyarakat terdiri dari beberapa tahap yaitu tahap pertama menentukan sampel terdiri dari 10 remaja dengan usia 12–19 Tahun. Tahap kedua menentukan alat ukur yang digunakan adalah kuesioner tingkat pengetahuan responden tentang gejala nyeri haid dan ketrampilan untuk mengurangi nyeri haid pada saat menstruasi. Tahap ketiga dilakukan ceramah dan diskusi maupun praktik secara online melalui WhatsappGrup. Tahap keempat mengaplikasikan yoga dengan melakukan pendampingan secara daring/online serta mengevaluasi dengan cara setiap remaja yang menjadi sampel mengirimkan video penerapan yoga.